P296 Levels of engagement in physical activity and fatigue in IBD patients. (16th January 2018) - Gatt, K; Schembri, J; Katsanos, K H; Christodoulou, D K; Balomenos, D; Karmiris, K; Pontas, C; Kopylov, U; Koutroubakis, I; Foteinogiannopoulou, K; Fábián, A; Molnár, T; et al.
Abstract: Background: IBD can greatly affect patients' work, personal and family lives, thus impacting on their quality of life. Regular physical activity may have a positive influence on one's fitness level, general wellbeing and psychological health. The aim of our study was to assess the levels of engagement in physical activity and fatigue in IBD patients pre- and post- diagnosis. Methods: We conducted a prospective multi-centre cross-sectional study were IBD patients diagnosed within the previous 18 months were recruited. Inclusion criteria included clinical remission and/or no treatment changes within the previous 6 months. Data were obtained through questionnaires which assessed clinical data, levels of exercise pre- and post-IBD diagnosis, functional assessment of chronic illness therapy (FACIT) and Godin physical activity scores. Results: 158 patients (CD – 100 patients; UC – 58 patients) from 7 different European centres were recruited. Mean age was 35.1 years (95% CI ± 2.0). Gender distribution was approximately equal (51.3% males). FACIT scores were lower in patients who had experienced relapses (38.1 [95% CI ± 2.7] p 0.012), severe disease (37.1 [95% CI ± 3.1] p 0.011) and in CD patients (38.9 [95% CI ± 2.4] p 0.095), though the latter failed to reach statistical significance. FACIT scores were not related to Godin scores or BMIs, either pre- or post- IBD diagnosis. 43.3% of IBD patients rarely (R) performed any exercise either before and after diagnosis. 42.3% of patients performed sports at an amateur (A) level and approximately 1/3 of them had a reduction in their activity level after their IBD diagnosis. A small amount of patients (3%) who rarely performed sports increased their physical activity post-diagnosis. 11.4% of patients performed sports either professionally (P) or semi-professionally (SP) pre-diagnosis and approximately 2/3 of these decreased their activity from P to SP and from SP to A. 46.1% of patients felt that medical professionals did not give enough importance to their level of fitness and a majority of patients (75.5%) considered it important that alternative methods to control their condition be discussed with them. Conclusions: While 37.8% of patients who performed sports at an amateur level or higher decreased their physical activity level post-IBD diagnosis, it is important to note that there was no correlation between FACIT scores and Godin scores. Thus the reduction in physical activity could be multifactorial and the impact of medical appointments and psychological factors needs to be assessed prospectively. Furthermore it would be important to discuss the possible roles of complementary and alternative therapies in clinic so as to avoid any possible misconceptions.